Can early postoperative intraocular pressure predict success following mitomycin-C augmented trabeculectomy in primary angle-closure glaucoma - Rong, S S (Nature Publishing Group, 2013)
PURPOSE: To evaluate the association between early and late postoperative intraocular pressure (IOP) and determine if early postoperative IOP can predict the surgical outcome. METHODS: A total of 165 consecutive patients with primary angle-closure glaucoma (PACG) undergoing primary mitomycin-C-augmented trabeculectomy underwent a comprehensive eye examination before surgery and were followed-up on days 1, 7, 14, and 30, and months 3, 6, 12, and 18. IOPs on days 1, 7, 14, and 30 were stratified into groups A (<10 mm Hg), B (≥10 and <15 mm Hg), C (≥15 and <20 mm Hg), and D (≥20 mm Hg). Differences between groups were analyzed using analysis of variance (ANOVA) and Fisher's exact test. Multivariable regression was used to exam the predictive ability of early IOP for final outcome. RESULTS: The mean age was 62.5±7.9 years and 41.21% (n=68) were males. Stratified by IOP on days 1, 7, 14, and 30, respectively, mean IOPs at month 18 were different among groups A, B, C, and D (ANOVA, P=0.047, P=0.033, P=0.008, and P<0.001, respectively). Once the IOPs were settled with interventions on day 7 a higher IOP level was associated with decreasing success rate under different outcome definitions, final IOP <15 mm Hg (Fisher's exact P=0.001) and <20 mm Hg (P=0.039) without medication. Multiple regression showed early IOP predicted final IOP independently from baseline variables. A cutoff value of 13.5 mm Hg on day 7 achieved an accuracy of 80.0 and 57.1% in predicting IOP<15 mm Hg without medication and failure after surgery, respectively. CONCLUSIONS: The IOP at 18 months following primary antifibrotic-augmented trabeculectomy in PACG patients is associated with and predicted by the postoperative IOPs at 1 month. Control of early IOP to 13.5 or less may provide better outcomes.